OBIS: online business information for the Pacific - Nowak, Moira (Technical Centre for Agricultural and Rural Cooperation, 2003)
Moira Nowak describes how a single computer connected to the Internet is helping farmers and rural entrepreneurs throughout the Solomon Islands to expand their businesses.